1999
DOI: 10.1098/rspb.1999.0739
|View full text |Cite
|
Sign up to set email alerts
|

Sequential mating patterns suggest extra–pair mating is not part of a mixed reproductive strategy by female red–winged blackbirds

Abstract: Studies aimed at determining why female birds often produce o¡spring sired by males other than their social mates generally compare traits of social and genetic mates. Here I examine paternity patterns in nests of the same female red-winged blackbirds (Agelaius phoeniceus) in successive breeding seasons. Returning females preferentially selected their former social mates as their new social mates when those males were present. However, paternity patterns were much less consistent. A female's behaviour (faithfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…This interaction between male age and neighbour's age is unexpected. It makes little sense from a female's perspective, and suggests that EPP by neighbours is not primarily a female‐driven event (supporting conclusions of Westneat 1992b and Weatherhead 1999) but rather emerges out of male–male interactions. For example, it is possible that males new to the study site invest considerably more in patrolling territory boundaries and guarding females than older males, but we have limited behavioural data on these males and so cannot assess this hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…This interaction between male age and neighbour's age is unexpected. It makes little sense from a female's perspective, and suggests that EPP by neighbours is not primarily a female‐driven event (supporting conclusions of Westneat 1992b and Weatherhead 1999) but rather emerges out of male–male interactions. For example, it is possible that males new to the study site invest considerably more in patrolling territory boundaries and guarding females than older males, but we have limited behavioural data on these males and so cannot assess this hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…These females exclusively chose one of the most attractive males of the population, suggesting that once females encounter very attractive males they can remate without additional sampling to limit search costs. Females of monogamous and resourcebased polygynous species commonly remain faithful and this has been related to past breeding success, the quality of the resources provided by mates and/or advantages to quick pair formation (see Black 1996;Weatherhead 1999). In polygynous species with no male parental care, however, there has been no previous evidence that male attractiveness, which probably re£ects his quality, in£uences mate ¢delity.…”
Section: (A) Dynamic Mate Searchingmentioning
confidence: 99%
“…However, the relation between female characteristics and EPP has received far less attention so far than the relationship between male characteristics and EPP (but see Westneat, 1992;Dunn et al, 1994;Wagner et al, 1996;Stutchbury et al, 1997;Cordero et al, 1999;Kempenaers et al, 1999;Weatherhead, 1999;Li & Brown, 2000;Veiga & Boto, 2000;Dickinson, 2001). Only three studies have reported female age to be correlated with the proportion of EPP in their broods.…”
Section: Introductionmentioning
confidence: 99%